A pipeline approach for three dimensional time-domain finite-difference multi-parameter waveform inversion on GPUs. (July 2020) - Le, Huy; Clapp, Robert G.; Levin, Stewart A.; Biondi, Biondo
Abstract: We adopt a pipeline approach to accelerate 3D time-domain finite-difference waveform inversion codes using graphics cards, thus avoiding domain decomposition. The key designs include streaming through the volume one block at a time and propagating this block as many time steps as possible while it is on the device. This approach allows us to process an arbitrarily large volume with a single GPU, which is particularly suitable in a cloud environment where fast inter-nodal connection is not guaranteed. Moreover, two parameters, block size and number of updates, give users flexibility to adapt to available resources at hand. The most significant advantage that the pipeline approach offers is the ability to compute subsurface offset gathers on GPUs. We describe our implementation on the pseudo-acoustic anisotropic wave equations and show that the pipeline technique achieves nearly linear scaling with number of GPUs. Application to multi-parameter anisotropic inversion on a 3D field data improves the quality of seismic image and flatness of offset gathers. Highlights: A pipeline algorithm for large-scale 3D time-domain finite-differences on GPU. Performance tests, implementation designs, speedup, and scaling with number of GPUs. An application to full-waveform inversion on a 3D seismic field data.